2004
DOI: 10.1007/s00421-003-0966-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ventilation pattern and pulmonary blood flow on lung heat transfer

Abstract: To investigate the relative role of pulmonary perfusion compared to ventilation on lung heat exchange, we determined the effects of blood flow, tidal volume and frequency of ventilation on the rate of lung heat transfer. In anesthetized dogs and isolated, perfused lungs, we investigated the dependence of the overall lung heat transfer coefficient (HTC) and lung thermal capacitance upon ventilation and pulmonary blood flow. The relationship between the HTC and pulmonary blood flow was strongly dependent on vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The results of the study by Serikov et al (2004) are in contrast with highly encouraging findings, reported by the same author in previous animal and human studies , where the s was not influenced by physiologic changes of minute ventilation (ventilation-to-perfusion ratio <5). The author also assumed the effective coefficient of lung thermal conductivity to be a constant and recommended a new non-invasive method for estimating cardiac output by simply measuring s. Serikov found an excellent correlation between cardiac output and the inverse s in 48 patients (r=0.89).…”
contrasting
confidence: 80%
See 2 more Smart Citations
“…The results of the study by Serikov et al (2004) are in contrast with highly encouraging findings, reported by the same author in previous animal and human studies , where the s was not influenced by physiologic changes of minute ventilation (ventilation-to-perfusion ratio <5). The author also assumed the effective coefficient of lung thermal conductivity to be a constant and recommended a new non-invasive method for estimating cardiac output by simply measuring s. Serikov found an excellent correlation between cardiac output and the inverse s in 48 patients (r=0.89).…”
contrasting
confidence: 80%
“…
Serikov and colleagues evaluated the effects of the ventilation pattern and pulmonary blood flow on lung heat transfer (Serikov et al 2004). The authors conclude that the pattern of ventilation substantially affects the values of the overall heat transfer coefficient of the lungs determined at the tracheal level, and thus limits the usefulness of measuring lung heat transfer for determining pulmonary blood flow.
…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the promising correlations, further extension of these studies into patients with mismatched ventilation and perfusion, low tidal volumes, and possible lung, bronchial or vascular pathology demonstrated that more complex relationships exist between simple indexes of lung heat exchange and pulmonary blood flow. To further clarify these relationships, we undertook this present animal study, combined with complex mathematical modeling, to determine whether there are limits to the use of a simple lumped-sum model of heat exchange (Serikov et al 2004). These results clearly indicate that the limitations of our previous simple model are substantial.…”
mentioning
confidence: 74%
“…We agree that pulmonary heat transfer is a promising parameter in critical care and pulmonary medicine. It should indeed be investigated and developed further from this biomechanical perspective and our publication (Serikov et al 2004) is intended to serve this goal.…”
mentioning
confidence: 98%